2018
DOI: 10.1111/iju.13527
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the landscape of urology: A new media‐based cross‐sectional analysis of public versus academic interest

Abstract: A quantification of academic and public interest in the urological field is feasible using a novel new media-based methodology. We found several mismatches in public versus academic interest in urological diseases and treatments, which has implications for research strategies, conference planning and patient information projects. Regular re-assessments of the public and academic interest landscape can contribute to detecting and proving trends in the field of urology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“… 5 Andrological urology is another topic of high public interest, but the available information in this field has not been adequately examined. 4 The purpose of our study is to formally assess the quality of information regarding erectile dysfunction (ED) in videos on YouTube. We hypothesize that the information is widely accessed by users but that it is likely to be of low quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Andrological urology is another topic of high public interest, but the available information in this field has not been adequately examined. 4 The purpose of our study is to formally assess the quality of information regarding erectile dysfunction (ED) in videos on YouTube. We hypothesize that the information is widely accessed by users but that it is likely to be of low quality.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is underlined by previous research showing that even on health-care provider websites, the quality of information is not always adequate and may sometimes be directly misleading. 3 Within urology, the condition of main public interest on YouTube is prostate cancer 4 and in a well-designed study, using validated assessment tools, Loeb et al recently found that the general quality of information in videos about prostate cancer is questionable and that many videos contain biases. 5 Andrological urology is another topic of high public interest, but the available information in this field has not been adequately examined.…”
Section: Introductionmentioning
confidence: 99%
“…The concern regarding the lack of awareness by urology, as well as primary healthcare physicians and the general public seems to be an international issue [11,12]. The FUSAG alongside the USANZ have instituted more teaching sessions on FU throughout training.…”
Section: Discussionmentioning
confidence: 99%
“…Borgmann et al could show a mismatch between the different perspectives and, for example, a very high public interest in andrological urology and higher academic interest in urologic oncology. Female and functional urology had a relatively higher academic interest with a ratio of 0.7 . Nevertheless, topics on functional urology might have the potential to integrate patients into the discussion due to the high impact on quality of life of diseases like urinary incontinence and, therefore, health care professionals should be more active on Twitter and provide high‐quality information.…”
Section: Discussionmentioning
confidence: 99%